2002
DOI: 10.1080/20025891107186
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Vapor Intrusion Into Buildings through a Study of Field Data

Abstract: A systematic examination of cases on file with the Massachusetts Department of Environmental

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 3 publications
0
45
2
Order By: Relevance
“…The assessment of extent and hazard posed by vapor intrusion of VOCs into buildings has received increasing attention in recent years (Murphy and Chan, 2011;Eklund et al, 2012;McHugh et al, 2012;Picone et al, 2012;Turczynowicz et al, 2012;Wang et al, 2012). With *500,000 contaminated sites in the United States presenting uncertain VOC vapor intrusion risk (Schuver, 2007), the assessment of risk from inhalation of these vapors has been a topic of recent discussion, field investigations (Fitzpatrick and Fitzgerald, 2002;Sanders and Hers, 2006;William et al, 2007), and modeling studies (Abreu and Johnson, 2005;DeVaull, 2007;Tillman and Weaver, 2007;Bozkurt et al, 2009;Pennell et al, 2009;Yao et al, 2011). In 2002, the U.S. EPA issued a draft guidance for vapor intrusion assessment (EPA, 2002), and new final guidance is imminent.…”
mentioning
confidence: 99%
“…The assessment of extent and hazard posed by vapor intrusion of VOCs into buildings has received increasing attention in recent years (Murphy and Chan, 2011;Eklund et al, 2012;McHugh et al, 2012;Picone et al, 2012;Turczynowicz et al, 2012;Wang et al, 2012). With *500,000 contaminated sites in the United States presenting uncertain VOC vapor intrusion risk (Schuver, 2007), the assessment of risk from inhalation of these vapors has been a topic of recent discussion, field investigations (Fitzpatrick and Fitzgerald, 2002;Sanders and Hers, 2006;William et al, 2007), and modeling studies (Abreu and Johnson, 2005;DeVaull, 2007;Tillman and Weaver, 2007;Bozkurt et al, 2009;Pennell et al, 2009;Yao et al, 2011). In 2002, the U.S. EPA issued a draft guidance for vapor intrusion assessment (EPA, 2002), and new final guidance is imminent.…”
mentioning
confidence: 99%
“…The arithmetic mean total VOC (TVOC) concentration was 829 µg/m 3 based on identified compounds; however, the concentration was estimated to be as high as 1.4 µg/m 3 if non-identified compounds were to be included (i.e., estimate based on area under the gas chromatograph trace). The mean indoor benzene concentration for this study was 5.4 µg/m 3 . On the basis of this study, it was concluded that toluene, ethylbenzene, xylenes, decane, and dichlorobenzene were chemicals with a high likelihood of originating from indoor sources; benzene had a medium likelihood; and tetrachloroethylene, trichloroethylene, and hexane had a low likelihood of indoor sources.…”
Section: Indoor Air Qualitymentioning
confidence: 99%
“…3 In this case, intrusion would be controlled by near-field processes. Several radon studies also suggest that radon intrusion by advection is typically a more significant process than is diffusion.…”
Section: Mechanisms For Soil Vapor Intrusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the fact that residential and commercial buildings have traditionally been designed for approximately one exchange of indoor air with outdoor air every hour (ASHRAE 1981), it is ironic that the contribution of outdoor air to indoor air benzene is largely ignored in federal and state regulatory practices. The majority of modeling studies attempting to account for indoor air benzene also focus on soil vapor intrusion (Turczynowicz and Robinson 2001, Hers et al 2002, Abreu and Johnson 2006, Fitzpatrick and Fitzgerald 2002, Freijer and Bloemen 2000, Hers et al 2003, even though the input from groundwater to indoor air has been strongly disputed (McHugh et al 2004), and others have concluded that indoor and outdoor air benzene are essentially at equilibrium in the absence of specific sources such as smoking or gasoline storage (Ilgen et al 2001, Kingham et al 2000. When either ground water or soil contamination is suspected from petroleum or manufactured gas plant (MGP) sources, site investigations normally only obtain samples of indoor air and soil gas and/or ground water benzene, and the contribution from outdoor air to indoor air benzene is ignored.…”
Section: Introductionmentioning
confidence: 99%